artificial intelligence in the arts : nr. 1 "brainwork". (Graz : Steirischer Herbst, 1985)
Kriesche, Richard ; Gerke, Peter ; Slopek, Edward ; Ascott, Roy ; Brock, Bazon ; Grundmann, Heidi
artificial intelligence in the arts : nr. 1 "brainwork", this book has been published in connection with the exhibition and the symposium taking place in los angeles, 1985
boek